Magnetic Resonance Angiography Determined Sex-Related Variations in Configuration of Entire Circle of Willis in Bengali Population of Chattogram Division (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2025)
Background: Magnetic Resonance Angiography (MRA) is a group of techniques based on Magnetic Resonance Imaging (MRI) for imaging of blood vessels. It’s the most widely used method for detecting the morphology of Circle of Willis (COW). By using the 3D-TOF-MRA the present study was aimed to evaluate the anatomical variations in the Circle of Willis between male and female in Bengali population of Chattogram division. Materials and methods: This cross-sectional observational study was conducted in the Department of Anatomy, Chittagong Medical College, Chattogram, upon 60 study subjects (29 were male & 31 were female) by dividing them intotwo groups (£40 years and >40 years of age). For statistical analysis unpaired student’s t-test was done and p-value was considered significant if it was